Family experience in implementing family center care for sick children in the special region of Yogyakarta - Susilo Adi, Giri; Pratiwi, Etik; Prihatin, Eni Septi Wulandari Dwi; Kustio Priliana, Wiwi (International Journal of Research in Medical Sciences, 2023)
Background: The family plays an important role in the hospitalization of children. Patient and family centered care (PFCC) or family care centered is an approach to planning, implementing, and evaluating health care that is based on mutual benefits. This study aims to knowing the experience of families in implementing family center care for sick children in the bantul area, special region of Yogyakarta. Methods: The research was implemented using the mixed method. The quantitative design was carried out using a pre-experimental design model with a pre-post-test and a qualitative method. The study sample consisted of 41 patients taken from a medical and rehabilitation clinic in the Yogyakarta area. A sample of 10 patients to examine the experiences of patients who experience pain. Results: The results of data analysis using the paired sample t test with the average FCC pretest score is 78.313, and the average FCC post test score is 79.980. The test results showed a p value of 0.00. Patient experience in family center care which includes giving affection, information about how to care for patients and providing nutrition to patients. Health workers can carry out periodic monitoring related to family center care activities so that families can meet the needs of children, especially when children are sick. Conclusions: Family center care program had effect on patient recovery.